Visual Languages: A New Way of Programming - Ahmad, Rodina (Malaysian Journal of Computer Science, 1999)
Visual programming languages(VPLs) represent quite the biggest departure from traditional programming approaches. However the last ten years have seen quite remarkable progress in this field. There is a number of visual programming languages (VPLs) already in the market and others are still in the research prototype stage and it is difficult to predict the suitability of its usage for the real world applications. This paper highlights some of the basic concepts of visual programming, its classification, current research trends and the benefits gained from using it.